(untitled) (Palíndromo, 2022)
This article aims to identify the academic training of effective teachers of Art at the Federal Institute of Paraná. It also proposes to check, together with the menus and analysis scripts of the pedagogical projects of the integrated technical courses (PPC) of the institution, to its main areas/lines of professional activity, in order to draw a profile of this faculty. For this, a qualitative, descriptive and data survey research was developed in documents published on the websites of the campuses and on the page of the Dean of People Management (PROGEPE). The study reveals that the IFPR is currently constituted in an institution with 26 campuses, with 43 effective teachers of Art, with diverse backgrounds in the area of art - although without any professional with specific training in Dance. There are cases of untrained professionals teaching the component, in addition to an extreme difficulty in legitimizing art teaching in the institutional context, sometimes due to an internal resistance of the management to recognize the relevance of the area for human and professional training, sometimes due to the unavailability of spaces suitable for educational practices in Art.